Impact of ponderosa pine afforestations on soil organic matter (SOM) in semiarid steppes of western Patagonia, Argentina - Buduba, Carlos Guillermo (2017)
The western steppe of Patagonia, Argentina, is being afforested with conifers since long ago. However, the effects of this land-use change on some soil parameters are still unknown. We determined soil organic matter (SOM) and root abundance at different soil depths, in 29 paired steppe-ponderosa pine (Pinus ponderosa Dougl. ex Laws.) stands planted at different times and densities between the 36°43′ and 44°8′S, and the 71°29′ and 70°35′W, in Patagonia, Argentina. SOM was significantly higher (p < 0.05) in steppe than in afforestations at upper soil horizons (0–30 cm soil depth), and similar at deeper depths. Soil OM was also higher in steppe as compared to sparse/young afforestation stands. Denser/older stands showed equal or slightly higher SOM values as compared to steppe. While root abundance was higher (p < 0.05) in afforestations than in steppe at all but in the superficial soil horizon, it has not yet significantly contributed to SOM formation. This study contributes to the understanding of how ponderosa pine afforestations, planted on a steppe of Patagonia, affect SOM, adding useful information for other areas of the world in which afforestations replace native vegetation.